Research of the residual bearing capacity and the work of damaged reinforced concrete beams' inclined sections - Kos, Željko (Array, 2020)
The article is devoted to studies about the stress-strain state and the residual bearing capacity of inclined sections of reinforced concrete beams with concrete damages in the compressed zone near support areas. The developed method of calculating the bearing capacity of the inclined sections of damaged beams is described. The numerical test of prototypes was performed in the LIRA-CAD 2017 software complex. A comparison of the results of laboratory tests, a numerical experiment and calculation results by the proposed method is shown. It is stressed that with an increase in the area of damage, the bearing capacity decreases. The nature of the change in the stress-strain state under the presence of damage is described. It is pointed out that in the damaged samples, there is an inclination of the neutral axis in the cross section of the element – it tilts, the neutral axis becomes, almost, parallel to the front of the damage.